PERUBAHAN POLA TATANAN RUANG TANEAN LANJANG DI KAMPUNG BATIK TANJUNG BUMI (The Changes of the Spatial Pattern of Tanean Lanjang in Kampung Batik Tanjung Bumi) - Muchlisiniyati Safeyah; Eva Elviana; Nurjanti Takarini; Aris Sutejo (Tesa Arsitektur, 2018)
Kampung batik of Tanjung Bumi has the uniqueness from the craft of batik gentongan and traditional settlement of tanean lanjang. Batik activities that originally as a filler of spare time, is currently done to earn income.The changes of paradigm is expected to have an impact on changing the pattern of arragement of tanean lanjang. The research was descriptive with qualitative method which was done on 6 (six) groups of tanean lanjang. The changes in the paradigm of society do not show much change in the pattern of arragement of tanean lanjang in the kampung batik of Tanjung Bumi. The tanean lanjang (the long of yard); fence; location, orientation, hierarchy, and shape of the Langgar; and the porch of houses are the elements that are preserved. The function of the Langgar becomes less. The spaces in the houses are private whereas the porch of the houses has changed on its character from semi-privat become semi-public. The changes happened on its pattern, total, and the function of the residential space which more complex. It is also much more influenced by development of life of social than the development of batik activities.The pattern of tanean lanjang can be a place of the develpment of batik activities. The traditional settlement of tanean lanjang is still suitable with the meaning the way of life today.